The inverted repeat as a recognizable structural feature in supercoiled DNA molecules. - Lilley, D M (1980)
The single-strand-specific endonuclease S1 from Aspergillus oryzae introduces highly selective cleavages into supercoiled covalently closed circular DNA molecules, but not into their previously linearized counterparts. The cleavage sites are inverted repeats of unit length between 9 and 13 base pairs, separated by a nonrepetitious 2-6 base pairs. Such regions may adopt hairpin or similar structures stabilized by the negative superhelix density and may constitute recognition sites for cellular proteins.